Navigating Fanaticism, Religiosity, and the Impact of Social Media Marketing on Anime Cosplay in Indonesia - Muchammad Saifuddin; Tania Amalia Khoirunnisa (Universitas Dinamika, 2026)
Aims: This study aims to examine the effects of fanaticism and religiosity on the purchasing behavior of anime cosplayers in Indonesia and to investigate the mediating role of social media marketing. Methodology : This study employed a quantitative explanatory research design using survey data collected from 260 anime cosplayers in Indonesia. The proposed research model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both direct and indirect relationships among the constructs. Findings : The results indicate that fanaticism has a positive and significant effect on purchasing behavior and social media marketing. Religiosity does not directly influence purchasing behavior but positively affects social media marketing. Furthermore, social media marketing positively influences purchasing behavior, partially mediates the relationship between fanaticism and purchasing behavior, and fully mediates the relationship between religiosity and purchasing behavior. Research Limitations/Implications : This study focuses exclusively on anime cosplayers in Indonesia, which may limit the generalizability of the findings to other cultural settings. The findings highlight the importance of social media marketing as a strategic mechanism for strengthening consumer engagement and translating consumers' religious values into purchasing behavior. Originality : This study extends Social Identity Theory by integrating fanaticism, religiosity, and social media marketing within the context of anime cosplay consumption. It provides new empirical evidence that social media marketing functions as a key mechanism linking religiosity with purchasing behavior in a fan-based community operating within a predominantly Muslim society.